Lycopodiaceae of the Guianas: List of exsiccata and distribution maps - Boudrie, Michel; Cremers, Georges; Øllgaard, Benjamin (Phytotaxa, 2023)
The present paper provides the detailed list of the specimens of Lycopodiaceae from the Guianas that we checked during the preparation of our paper published in 2020, as well as their distribution maps. A total of 603 specimens have been studied corresponding to 28 taxa in five genera (Lycopodiella, Lycopodium, Palhinhaea, Phlegmariurus, Pseudolycopodiella). An additional species, Phlegmariurus tenuicaulis, is added and the combination of Pseudolycopodiella meridionalis var. mesetarum, which was invalid in our previous paper, is here validated.